Evaluation of Histopathologic Role in Providing Cause of Death in Sudden Unexpected Natural Death - Lakshmi K, Sree; N, Ashalatha; VenkataRaghava, S; A R, Raghupathi; Biligi, Dayananda S; Ahmed, Siddique M; M , Natarajan (Journal of Indian Academy of Forensic Medicine, 2014)
Sudden unexpected natural death in an adult is an issue of great concern for medical  professionals. Cardiovascular pathology is the most common cause of sudden death. However, no  definitive cause of death can be found at post-mortem and subsequent histopathologic examination in a  minority of cases. The present study aims to evaluate the role of a histopathologist in providing a  conclusive cause of death, to assess the percentage of cases where a conclusive diagnosis could not be  offered, age and sex distribution of the cases of sudden death and compare the data with that obtained in  other studies. Data from our study showed 89.77% male deaths. Seventy five percent of deaths were  seen in < 40 years of age. Maximum number of cases (39.77%) was seen in second decade followed by  third decade (26.13%). Cardiac causes of sudden death accounted to 69.13% of the cases. Non cardiac  causes contributed 11.36% of cases. In 19.31% cases even after detailed histopathologic examination  cause of death could not be concluded.
Keywords: Sudden death; Histopathology; Negative autopsy; Cardiac; Non cardiac